What is the High School discent understanding about the evolutionary process? An analysis carried out at a public school of the federal network (Research, Society and Development, 2020)
The biodiversity of organisms is the result of biological evolution. Evolutionary processes are intertwined with the most varied areas of biology, which demonstrates the importance of this knowledge for the understanding of innumerable biological phenomena. Despite this, it is notorious in several situations, the difficulty of students in understanding the main aspects of the evolutionary process. This work had as objective to analyze the conceptions about the evolutionary process of the students of the integrated technical high school of a public school of the federal network. 137 students participated in this research, being interviewed through a questionnaire composed of seven items. The results demonstrate that the students incorrectly associate the evolutionary process with the terms: improvement, progress or complexity, in addition to having difficulties in associating evolution with other areas of biology. It is recommended that the contents to be taught during this stage of basic education occur in an articulated manner, in order to reduce the difficulties mentioned.